2009
DOI: 10.3892/or_00000434
|View full text |Cite
|
Sign up to set email alerts
|

A low number of tumor-infiltrating FOXP3-positive cells during primary systemic chemotherapy correlates with favorable anti-tumor response in patients with breast cancer

Abstract: Abstract. Cancer cells induce proliferation and local accumulation of immunosuppressive cells, such as FOXP3-positive cells known as regulatory T cells (Tregs), leading to tumorinduced immune tolerance. Although cancer chemotherapy is usually considered immunosuppressive, some chemotherapeutic agents activate an anticancer immune response. Therefore, we postulated that the number of tumor-infiltrating FOXP3-positive cells during primary systemic chemotherapy (PSC) correlates with therapeutic outcomes in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…They demonstrated that lymph vessel invasion was prominent in the group with a high number of FoxP3 infiltrates [79].…”
Section: Possible Functions Of the T Cells In Disseminated Breast Cancermentioning
confidence: 99%
“…They demonstrated that lymph vessel invasion was prominent in the group with a high number of FoxP3 infiltrates [79].…”
Section: Possible Functions Of the T Cells In Disseminated Breast Cancermentioning
confidence: 99%
“…To date, several studies of breast cancer have shown a consistent association between FOXP3 + TIL and poor clinical outcome (Bates et al , 2006; Aruga et al , 2009; Gobert et al , 2009; Liu et al , 2011; Yan et al , 2011; Mahmoud et al , 2011b). Although none of these studies focused on specific histological or molecular subtypes of breast cancer, FOXP3 + TIL showed a consistent association with ER-negative (ER–) tumours, which are biologically and clinically distinct from ER+ lesions (Foulkes et al , 2010).…”
mentioning
confidence: 99%
“…In the end, we reviewed 58 studies encompassing 16 different cancer types (Table 1), including bladder (19), breast (21)(22)(23)(24)(25)(26)(27)(28), cervical (29,30), colorectal (12,(31)(32)(33)(34)(35)(36)(37)(38)(39), endometrial (40)(41)(42), gastric (14,(43)(44)(45)(46), head and neck (47), hepatocellular (48)(49)(50)(51)(52), lung (53,54), melanoma (55)(56)(57)(58), mesothelial (59), oral (4,(60)(61)(62)(63), ovarian (2,3,…”
Section: Introductionmentioning
confidence: 99%